A microwell array platform to print and measure biomolecules produced by single cells. Issue 10 (1st May 2019) - Abali, Fikri; Broekmaat, Joska; Tibbe, Arjan; Schasfoort, Richard B. M.; Zeune, Leonie; Terstappen, Leon W. M. M.
Abstract : Here we describe a combined method to monitor the secretion of molecules produced by single cells, followed by a method to isolate the individual cells that produced these molecules. Abstract : Here we describe a combined method to monitor the secretion of molecules produced by single cells, followed by a method to isolate the individual cells that produced these molecules. The method is based on a self-sorting microwell chip that is connected to an activated membrane that collects the produced molecules. The produced molecules are printed by diffusion in small spots onto the membrane. The location of the printed spots can be correlated to the microwell number and the cell that produced these molecules. To demonstrate the method, we used the EpCAM antibody producing hybridoma cell line VU1D9 and a genetically engineered CHO cell-line producing Her2. VU1D9 cells produced 4.6 ± 5.6 pg (mean ± SD) of EpCAM antibody per 24 h and CHO cells 6.5 ± 8.2 pg per 24 h of Herceptin antibody.